Dynamics of Off-Farm Employment in Sub-Saharan Africa : A Gender Perspective - Van den Broeck, Goedele; Kilic, Talip (World Bank, Washington, DC, 2018)
Off-farm income constitutes a significant share of the household livelihood portfolios across Sub-Saharan Africa. Yet, the determinants and dynamics of individuals' participation in off-farm employment activities have not received adequate attention due to the weaknesses in individual-level data collection and the lack of longitudinal studies. This paper uses national panel household survey data from Ethiopia, Malawi, Nigeria, Tanzania, and Uganda; provides empirical evidence on individual-level off-farm (wage and self) employment participation rates; analyzes the extent and drivers of entry into off-farm employment and continued employment; and conducts the analysis by gender and rural/urban location. A significant share of the rural and urban working-age individual population is found to participate in off-farm employment, ranging at the national level from 34 percent in Ethiopia to 58 percent in Malawi. Men participate in wage and self-employment to a significantly greater extent compared with women across time as well as within and across countries, apart from women's participation in non-farm enterprises being more common in Nigeria and Tanzania. The population weighted cross-country gender difference in off-farm employment stands at 9 percentage points, but this has declined over time in most countries. A substantial share of the population, amounting to about 39 million individuals across the five countries, is estimated to have entered and exited employment between 2010 and 2016, pointing to the dynamic nature of off-farm employment. Drivers of entry into off-farm employment and continued employment are country- and gender-specific, with demographic factors, occurrence of shocks, and job characteristics emerging as the most important determinants.